1992
DOI: 10.1136/bmj.304.6838.1347
|View full text |Cite
|
Sign up to set email alerts
|

Survey of 3765 cardiopulmonary resuscitations in British hospitals (the BRESUS Study): methods and overall results.

Abstract: Objective-To determine the circumstances, incidence, and outcome of cardiopulmonary resuscitation in British hospitals.Design-Hospitals registered all cardiopulmonary resuscitation attempts for 12 months or longer and followed survival to one year.Setting-12 metropolitan, provincial, teaching, and non-teaching hospitals across Britain.Subjects-3765 patients in whom a resuscitation attempt was performed, including 927 in whom the onset of arrest was outside the hospital.Main outcome measure-Survival after initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
6
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(125 citation statements)
references
References 23 publications
7
105
6
7
Order By: Relevance
“…The subset of 10 studies meeting the strict inclusion criteria included 2,434 patients. Among the 41 studies that met the minimal criteria, 12 took place in Europe, 13,15,17,19,28,31,38,[40][41][42][43][44]48 one each in Australia, 22 Israel, 24 and Japan, 30 12 (1983) 294 All adults Y x x x Gulati et al 13 (1983) 52 Adults Ն age 64 N x Scaff et al 14 (1984) 242 All adults N x x Sowden et al 15 (1984) 108 All adults N x ? ?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subset of 10 studies meeting the strict inclusion criteria included 2,434 patients. Among the 41 studies that met the minimal criteria, 12 took place in Europe, 13,15,17,19,28,31,38,[40][41][42][43][44]48 one each in Australia, 22 Israel, 24 and Japan, 30 12 (1983) 294 All adults Y x x x Gulati et al 13 (1983) 52 Adults Ն age 64 N x Scaff et al 14 (1984) 242 All adults N x x Sowden et al 15 (1984) 108 All adults N x ? ?…”
Section: Discussionmentioning
confidence: 99%
“…However, only six studies were identified in a review of the literature that reported results for more than 500 patients, and only one included more than 1,000 patients. 10,36,41,43,47,56 Therefore, the majority of studies have had inadequate sample size to identify important predictors of the outcome of in-hospital CPR. Although smaller studies have shown relations between pre-arrest variables and the outcome of CPR, those associations have been inconsistent.…”
Section: Jgimmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] The overwhelming majority of eventual survivors come from this group. [15][16][17][18] If the definitive treatment for these arrhythmias-defibrillation-can be implemented promptly a perfusing cardiac rhythm may be restored and lead to long term survival. The only interventions that have been shown unequivocally to improve long term survival are basic life support and defibrillation.…”
Section: Defibrillationmentioning
confidence: 99%
“…The published outcomes for outof-hospital pediatric cardiac arrest are dismal; survival to hospital discharge occurs in approximately <10% of children, and many have severe neurologic sequelae. [59][60][61][62][63] Poor outcomes may be related to prolonged periods of no cardiac output, in part because many out-of-hospital arrests are unwitnessed, and only approximately 30% of children received bystander CPR 61 (note also that bystander CPR more than doubles patient survival rates 64 ).…”
Section: Secondary Prevention Of Scamentioning
confidence: 99%